THE BARRIERS FACING BLACK WOMEN ACADEMICS AT UNISA POST 2006 - Dube, Gwendolene Thobela (My University, 2014)
Black women academics at the University of South Africa (UNISA) are faced with the same challenges as other women in leadership positions in academic institutions have to contend with. At UNISA there are institutional and individual barriers, namely, criteria for promotion, lack of support, limited networks and inadequate mentoring programmes, to mention but a few. These barriers militate against their professional development; so there is paucity of Black women leaders in top management at UNISA. Women leadership has always been a contested terrain. The literature on women in higher education attest to the fact that there are few women in leadership positions and this is a trend worldwide. Women leadership is always associated with empowerment, access to equal opportunity for advancement of employment equity. In addition women academics felt that they are in spaces that were not created for them and that is why they have to prove themselves that they are equally capable to becoming scholars of note like their peers. There have been some changes at UNISA which may improve the situation for women leaders, like formal development programmes are established in order to redress the legacy of the past. There is a need to change the mindset of the both academics and administrators so that UNISA is a home for all.
MM (P&DM) thesis
Keywords: Women in leadership; Women academics